Handbook of research on network forensics and analysis techniques - Shrivastava, Gulshan 1987-; Kumar, Prabhat; Gupta, B. B.; Bala, Suman; Dey, Nilanjan 1984- (Advances in information security, privacy, and ethics (AISPE) book series, 2018)
"This book explores the latest advances in network forensics and analysis techniques. It explores topics such as network security: attacks and controls, analysis of attacks, defenses, and countermeasures, anonymity, privacy, id theft and ethics, dependability and security forensics, denial-of-service, and botnet analysis, detection, and mitigation"...